HIGHER EXCITED STATES OF α+α SYSTEM - M. Odsuren,; A.T. Sarsembayeva,; G. Khuukhenkhuu,; S. Davaa,; K. Kato,; B. Usukhbayar, (Academic Scientific Journal of Computer Science, 2019)
In this work we investigate the higher excited states of + system applying the complex scaling method. The low-lying 0+ , 2+ and 4+ states of + are measured well but the higher excited states 6+ , 8+ and 10+ of + are not available by experimentally and these higher excited states have been barely studied by theoretical approaches.